2018
DOI: 10.1037/pri0000060
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial psychometrics of a school-based screening program to prevent adolescent suicide.

Abstract: Practice Innovations is a publication of APA Division 42 (Psychologists in Independent Practice). Published quarterly (beginning in March), PI serves practitioners by publishing clinical, practical, and research articles on current and evolving standards, practices, and methods in professional mental health practice. Designed as a cross-disciplinary publication with a multi-theoretical scope, the journal supports innovation and the highest standards of care in mental health practice. Coverage areas include pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…Mechanisms to connect identified children to support is the critical final step in any identification program ( Dvorsky et al, 2014 ), yet details of this phase are often unreported in studies of program effectiveness ( Anderson et al, 2018 ). When such post-identification results are reported, they are not promising; previous studies show that up to one half of children identified in school-based programs do not receive further evaluation or support ( Gould et al, 2009 ; Hilt et al, 2018 ; Nemeroff et al, 2008 ). In their study of service use after school-based suicide screening, Gould et al (2009) found several barriers for accessing care among CYP who screened positive.…”
Section: Discussionmentioning
confidence: 94%
“…Mechanisms to connect identified children to support is the critical final step in any identification program ( Dvorsky et al, 2014 ), yet details of this phase are often unreported in studies of program effectiveness ( Anderson et al, 2018 ). When such post-identification results are reported, they are not promising; previous studies show that up to one half of children identified in school-based programs do not receive further evaluation or support ( Gould et al, 2009 ; Hilt et al, 2018 ; Nemeroff et al, 2008 ). In their study of service use after school-based suicide screening, Gould et al (2009) found several barriers for accessing care among CYP who screened positive.…”
Section: Discussionmentioning
confidence: 94%
“…(1) Universal screening programmes Eight studies of universal screening programmes reported on rates of identification (Tisher, 1995;Jones et al, 2002;Gould et al, 2009;Robinson et al, 2010;Husky et al, 2011;Morey et al, 2015;Hilt et al, 2018). In six studies, positive screening results were verified by subsequent clinical interview conducted by MH professionals (Gould et al, 2009;Robinson et al, 2010;Husky et al, 2011;Morey et al, 2015;Hilt et al, 2018), or an existing diagnosis of MHD (Tisher, 1995), giving a reliable rate of false positives.…”
Section: Rates Of Accurate Identificationmentioning
confidence: 99%
“…Although a number of studies indicated that a referral was made for students identified as being at-risk, only three studies reported numbers and uptake of referrals to specialist support (Gould et al ., 2009; Husky et al ., 2011; Hilt et al ., 2018). All three studies evaluated universal screening for risk of suicide, although referral processes and services offered varied by programme.…”
Section: Rates Of Referrals and Service Uptakementioning
confidence: 99%
See 2 more Smart Citations